2015
DOI: 10.1186/s12970-014-0066-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of turmeric (Curcumin) supplementation on cytokine and inflammatory marker responses following 2 hours of endurance cycling

Abstract: BackgroundEndurance exercise induces IL-6 production from myocytes that is thought to impair intracellular defence mechanisms. Curcumin inhibits NF-κB and activator protein 1, responsible for cytokine transcription, in cell lines. The aim of this study was to investigate the effect of curcumin supplementation on the cytokine and stress responses following 2 h of cycling.MethodsEleven male recreational athletes (35.5 ± 5.7 years; Wmax 275 ± 6 W; 87.2 ± 10.3 kg) consuming a low carbohydrate diet of 2.3 ± 0.2 g/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 40 publications
4
63
1
2
Order By: Relevance
“…The present investigation demonstrated that a 1-h rowing ergometer exercise with an average EE of 639 ± 69 kcal caused significant post-exercise increases in IL-6, IL-8, VEGF and MCP-1 concentrations, whereas the mean concentrations of 8 out of 12 inflammatory biomarkers were not changed (P > 0.05) immediately after the endurance rowing session in college-level female rowers. Therefore, the magnitude of increase in IL-6 (ES = 0.64) and IL-8 (ES = 0.64) appeared to be moderate but similar to previous studies in athletes after acute endurance exercise [34,41]. The largest increases in IL-6 and IL-8 concentrations have been observed after prolonged severe exercise like marathon running [28,42].…”
Section: Discussionsupporting
confidence: 86%
“…The present investigation demonstrated that a 1-h rowing ergometer exercise with an average EE of 639 ± 69 kcal caused significant post-exercise increases in IL-6, IL-8, VEGF and MCP-1 concentrations, whereas the mean concentrations of 8 out of 12 inflammatory biomarkers were not changed (P > 0.05) immediately after the endurance rowing session in college-level female rowers. Therefore, the magnitude of increase in IL-6 (ES = 0.64) and IL-8 (ES = 0.64) appeared to be moderate but similar to previous studies in athletes after acute endurance exercise [34,41]. The largest increases in IL-6 and IL-8 concentrations have been observed after prolonged severe exercise like marathon running [28,42].…”
Section: Discussionsupporting
confidence: 86%
“…EIMD leads to the onset of an inflammatory response that is associated with a decrease in the ability to generate muscle strength, decreased range of motion (ROM), localized swelling, delayed onset muscle soreness (DOMS), and increased muscle proteins in the blood (creatine kinase (CK), lactate dehydrogenase (LDH), and myoglobin (Mb)) [3]. In addition, EIMD triggers inflammatory responses that result in elevations of inflammation markers such as C-reactive protein (CRP) and some inflammatory interleukins (IL-1, IL-6, tumor necrosis factor (TNF-α)) [4]. Similarly, it promotes the production of transcription factors such as nuclear factor kB (NF kB) through the production of reactive oxygen species (ROS) [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, curcumin is also widely used in sport and exercise physiology fields [11,12]. Some of the curcumin's potentials are as an anti-fatigue and recovery booster substance [13][14][15][16][17][18][19]. The term of fatigue that's explained before is a fatigue caused by workload or exercise and related to human physiological functions/physiological fatigue [20].…”
Section: Introductionmentioning
confidence: 99%
“…As the definition of fatigue described above, some studies related to curcumin as an anti-fatigue and recovery booster are divided into two groups. Several studies [13][14][15][16][17][18][19] examined the effect of curcumin related to central fatigue. The study concluded that curcumin can significantly reduce central fatigue indicators such as IL-6 and IL-1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation